A Brief Talk on the Condition of How Learners in Medan Learn the Blade-palatal Initials in Standard Chinese - Antony Hardi (Journal of Language, Literature and Teaching, 2019)
Blade-palatal initials zh[ʈʂ], ch[ʈʂh], sh[ʂ], and r[ʐ] are important characteristics in Standard Chinese (Putonghua) pronunciation, which are also some difficult parts for non-Chinese speakers. This paper is intended to analyze the appearance and condition of the blade-palatal-initial pronunciation of learners in Medan, Indonesia, in which the learners are divided into two groups, Chinese Indonesians and locals. It also describes the brief differences between Standard Mandarin and Southern Min initials and between Standard Mandarin initials and Indonesian consonants. To achieve the objective, the research was conducted by using descriptive-qualitative design. Because there are no blade-palatal sounds either in Indonesian or in Southern Min, it is very common for Chinese descendants in Medan who speak Putonghua to always omit the blade-palatal parts, e.g.: “to eat” that should be pronounced as [ʈʂhʅ55] to always be pronounced as [ʦhəʔ], which is not correct and might lead to another meaning. As well as locals who speak Indonesian to always replace the blade-palatal sounds with the consonants which sound near to them: [ʦə], [ʦhə], [sə],[rə].